Numerical investigation of heat transfer and fluid flow characteristics of an internally ribbed tube / Kailash Mohapatra and Dipti Prasad Mishra - Mohapatra, Kailash; Mishra, Dipti Prasad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
Numerical investigation have been performed by solving the conservation equations of mass, momentum, energy with two equation based k-e model to determine the wall temperature, outlet temperature and Nusselt number of an internally ribbed tube. It has been found from the numerical investigation that the heat transfer and pressure drop is increased by increasing the rib height and rib number. It was also found that there exists an optimum angle of inclination for maximum heat transfer and minimum pressure drop. The heat transfer is found to be highest in triangular rib compare to other shape.